ACTIVITY COSTING SYSTEM DALAM PENENTUAN BIAYA PENDIDIKAN ( STUDI KASUS PADA SMP 4 KOTA BANGUN ) - Mursalin, Haris Eko (EKONOMIA, 2013)
Application Analysis of Activity Costing System In Determining of Education Cost ( Case Study on SMP 4 Kota Bangun ). Junior High School 4 is a general school with many programs that initiated by the school has impact on operational costs. The cost of education only determined based on result of Committee meetings all this time. The problems arise up in this studyis it any difference between the cost of education that applied in the Junior high school 4 Kota Bangun with the cost of education based activity costing system.The purposeof this study is to see the difference between the cost of education is implemented by SMP 4 Kota Bangun with the cost of education based on Activity Costing System.For the purposes of analysis and discussion, the authors useanalytical tools named Activity Costing System. Activity Costing Systemis accost calculation tool in the economic approach. According to this economical approach, cost is a reflection of activities under taken by relatedentities, details of the cost is an activity and the necessary infrastructure to supportthe activity.